Financial Burden of Drugs Prescribed for Cancer-Associated Symptoms. Issue 2 (February 2022) - Gupta, Arjun; Nshuti, Leonce; Grewal, Udhayvir S.; Sedhom, Ramy; Check, Devon K.; Parsons, Helen M.; Blaes, Anne H.; Virnig, Beth A.; Lustberg, Maryam B.; Subbiah, Ishwaria M.; Nipp, Ryan D.; Dy, Sydney M.; et al.
Abstract : PURPOSE: The financial toxicity of anticancer drugs is well-documented, but little is known about the costs of drugs used to manage cancer-associated symptoms. METHODS: We reviewed relevant guidelines and compiled drugs used to manage seven cancer-associated symptoms (anorexia and cachexia, chemotherapy-induced peripheral neuropathy, constipation, diarrhea, exocrine pancreatic insufficiency, cancer-associated fatigue, and chemotherapy-induced nausea and vomiting). Using GoodRx website, we identified the retail price (cash price at retail pharmacies) and lowest price (discounted, best-case scenario of out-of-pocket costs) for patients without insurance for each drug or formulation for a typical fill. We describe lowest prices here. RESULTS: For anorexia and cachexia, costs ranged from 5 US dollars (USD; generic olanzapine or mirtazapine tablets) to 1, 156 USD (brand-name dronabinol solution) and varied widely by formulation of the same drug or dosage: for olanzapine 5 mg, 5 USD (generic tablet) to 239 USD (brand-name orally disintegrating tablet). For chemotherapy-induced peripheral neuropathy, costs of duloxetine varied from 12 USD (generic) to 529 USD (brand-name). For constipation, the cost of sennosides or polyethylene glycol was <15 USD, whereas newer agents such as methylnaltrexone were expensive (1, 001 USD). For diarrhea, the cost of generic loperamide or diphenoxylate-atropine tablets was <15 USD. For exocrine pancreatic insufficiency, only brand-name formulations were available, range of cost, 1, 072 USD-1, 514 USD. For cancer-associated fatigue, the cost of generic dexamethasone or dexmethylphenidate was <15 USD, whereas brand-name modafinil was more costly (1, 284 USD). For a 4-drug nausea and vomiting prophylaxis regimen, costs ranged from 181 USD to 1, 430 USD. CONCLUSION: We highlight the high costs of many symptom control drugs and the wide variation in the costs of these drugs. These findings can guide patient-clinician discussions about cost-effectively managing symptoms, while promoting the use of less expensive formulations when possible.